AKIBAT HUKUM PENGHAPUSAN ROYA HAK TANGGUNGAN PADA PERJANJIAN KREDIT DALAM PRAKTIK PERBANKAN - Nurmawati, Nurmawati; Musjtari, Dewi Nurul (Varia Justicia, 2020)
Roya is charged to the debtor without notifying that there is an additional obligation after paying off the mortgage. The aim of this research what are the legal consequences for the debtor if did not Roya in the implementation of the credit contract in PD BPR Bank Bantul. The metode of this research by using the empirical juridical method and qualitative analysis, the author examines primary data from interview with debtor, creditor and National Land Agency which combined with secondary data. The research shows that the legal protection for the debtor in the implementation of Roya are provided in Article 18 of Law Number 8 of 1999 on Consumer Protection, a protection for customer from exemption clause in a standard contract. The contract that violate this law shall be considered as null and void. Article 22 of Law Number 4 of 1996 on Mortgage stated that the plea for Roya is submitted by the interested party which translated as the creditor. The legal consequences if the debtor did not do the Roya is that the Land Certificate still administratively considered as a mortgage and the owner of the certificate of land cannot take any legal action on it.